2021
DOI: 10.1051/0004-6361/202039044
|View full text |Cite
|
Sign up to set email alerts
|

Small glitches and other rotational irregularities of the Vela pulsar

Abstract: Context. Glitches are sudden increases in the rotation rate ν of neutron stars, which are thought to be driven by the neutron superfluid inside the star. The Vela pulsar presents a comparatively high rate of glitches, with 21 events reported since observations began in 1968. These are amongst the largest known glitches (17 of them have sizes Δν/ν ≥ 10−6) and exhibit very similar characteristics. This similarity, combined with the regularity with which large glitches occur, has turned Vela into an archetype of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…Δ𝜈 𝑔 /𝜈 10 −6 ) interspersed between them. Glitches of similar amplitudes are seldom seen among the Vela-like pulsars, and indeed Vela itself appears to have a real under-abundance of small amplitude glitches (Howitt et al 2018;Espinoza et al 2021). A potential clue as to why these pulsars do not possess detectable large 𝑛, despite being situated near the Vela-like population in 𝑃-𝑃 space, comes from the lack of consistently large Δ 𝜈 𝑔 components associated with our glitch measurements in Table 2.…”
Section: Pulsars With Seemingly Small Braking Indicesmentioning
confidence: 80%
“…Δ𝜈 𝑔 /𝜈 10 −6 ) interspersed between them. Glitches of similar amplitudes are seldom seen among the Vela-like pulsars, and indeed Vela itself appears to have a real under-abundance of small amplitude glitches (Howitt et al 2018;Espinoza et al 2021). A potential clue as to why these pulsars do not possess detectable large 𝑛, despite being situated near the Vela-like population in 𝑃-𝑃 space, comes from the lack of consistently large Δ 𝜈 𝑔 components associated with our glitch measurements in Table 2.…”
Section: Pulsars With Seemingly Small Braking Indicesmentioning
confidence: 80%
“…Espinoza et al (2014) employed an automated glitch detection algorithm to search for glitches in the Crab pulsar, and reported a minimum glitch size in that case, which is intrinsic to the pulsar and not an artifact of the detector performance. This technique 6 http://www.jb.man.ac.uk/pulsar/glitches/gTable.html has also been applied to the Vela pulsar, and a lack of small glitches was reported in that case also (Espinoza et al 2021). However, the detector returns a large number of (anti-)glitch candidates which must be classified after the fact as timing noise or glitches.…”
Section: Population-level Comparisonmentioning
confidence: 98%
“…Espinoza et al (2014) and Yu & Liu (2017) employed automated glitch detection methods to evaluate detectability limits. The technique presented by Espinoza et al (2014) has been applied to timing data from the Crab and Vela pulsars (Espinoza et al 2021), while the technique presented by Yu & Liu (2017) was tested on simulated data but not used to search for glitches in real datasets. Most recently, Singha et al (2021) have developed an real-time glitch detection pipeline which operates with minimal human intervention and incorporated it into the timing programme at the Ooty Radio Telescope.…”
Section: Introductionmentioning
confidence: 99%
“…These deviations consist of relatively large steps in spin frequency, known as glitches, and smaller deviations often known as timing noise, not normally resolved into individual events. Espinoza et al (2014Espinoza et al ( , 2021 have added to this picture by identifying a population of small timing events, that could be interpreted as spin-ups, smaller than previously resolved glitches, which clearly form a separate population of events from glitches. They also found evidence for similar small spin-down events.…”
Section: Introductionmentioning
confidence: 99%
“…
Recently, Espinoza et al (2014Espinoza et al ( , 2021 reported the existence of "glitch candidates" and "anti-glitch candidates" which are effectively small spin-ups and spin-downs of a neutron star with magnitudes smaller than those seen in typical glitches. The physical origin of these small events is not yet understood.
…”
mentioning
confidence: 99%